Effect of Interstage Pipeline on the Performance of Two-Stage Centrifugal Compressors for Automotive Hydrogen Fuel Cells - Huaiyu Wang; Dengfeng Yang; Zhengcan Zhu; Hongjie Zhang; Qian Zhang (Applied Sciences, 2022)
At present, two-stage centrifugal compressors based on air bearing and high-speed motor technology are widely used in automotive hydrogen fuel cells. The low-pressure stage and high-pressure stage of the compressor are directly connected through an interstage pipeline, thus the structure of the interstage pipeline has an important influence on the aerodynamic performance of the compressor. In this work, a two-stage compressor with three different interstage pipelines were investigated experimentally and numerically. Results show that affected by the interstage pipeline bend section, the flow distortion will be induced at the impeller inlet of the high-pressure stage, and the distortion intensity changes with the pipeline structure. Among the three models, the EPC (elbow pipe change) model induces the most intense total pressure distortion at the condition of 80 kr/min and 130% mass flow rate, resulting in an efficiency reduction of 2 and 1.5 percentage points compared with the SPC (straight pipe change) and the TPC (total pipe change) model, respectively. Further research indicates that the upstream distortion has obvious influence on the downstream rotor blades. As the blade height decreases, the load becomes more uniform on the main blades, while the load extremum migrates to the trailing edge on the splitter blades. Finally, three models are tested, and their performance is compared at three typical rotational speeds., It is recommended that interstage pipelines similar to SPC models should be chosen to improve the two-stage compressor efficiency in the design.